A household-level demand system analysis of nuts in the United States. (7th August 2022) - Bakhtavoryan, Rafael; Cheng, Guo "Chris"; Capps, Oral; Dharmasena, Senarath
Abstract: An Exact Affine Stone Index demand model is estimated to analyze the household-level demand for nine nut products (peanuts, pecans, almonds, cashews, walnuts, pistachios, mixed nuts, macadamia nuts, and other nuts) in the United States using Nielsen Homescan panel data from 2009 through 2015. The demands for all nuts are elastic. All nut products are necessities and substitutes for each other. Household sociodemographic characteristics are statistically significant drivers of the demand for nut products. Finally, the effects of changes in the magnitude of selected promotion expenditure elasticities for nuts are simulated to determine their impacts on prices and quantities demanded.